Association of Discrimination and Stress With Cardiometabolic Risk Factors in Ethnic Minority Women. (December 2017) - Shin, Cha-Nam; Soltero, Erica; Mama, Scherezade K.; Sunseri, Christopher; Lee, Rebecca E.
Psychological stressors can contribute to adverse health outcomes and lead to health disparities. To examine associations among psychological stressors, coping, blood pressure, body mass index, and body fat in ethnic minority women, we conducted a secondary analysis using data from 178 African American and Hispanic/Latina women who completed measures of perceived racial discrimination and stress, coping, blood pressure, and body composition. The mean age of participants was 45.3 (±9.3 years), and most were obese (74.2%) and had prehypertensive systolic blood pressure (125.7 ± 14.6 mmHg). Hierarchical multiple regression models indicated a significant negative relationship between racial discrimination and percent body fat, and positive associations between stress and blood pressure. Coping did not moderate the association between racial discrimination and blood pressure or body composition. Health care providers should consider psychological stressors as underlying causes for hypertension and address tailored stress-reduction coping strategies when treating African American and Hispanic/Latina women with hypertension.